Roberto Rossellini's the flowers of St. Francis - Rossellini, Renzo 1908-1982 (<<The>> Criterion Coll., 2005)
"In a series of simple and joyous vignettes, director Roberto Rossellini and co-writer Federico Fellini lovingly convey the universal teachings of The People's Saint: humility, faith, and sacrifice. Gorgeously photographed to evoke the medieval paintings of Saint Francis' time, and cast with monks from the Nocera Inferiore Monastery" -- Container.
Aspect ratio 1.33:1. - New, restored high-definition digital transfer
Orig.: Italien 1950
Enth. exlusive new video interviews, conducted in 2004, with actress Isabella Rossellini, film historian Adriano Aprà and film critic Father Virgilio Fantuzzi ; the American-release prologue, situating the film in its historical context through paintings and frescoes
Keywords: Francis <of Assisi, Saint, 1182-1226> -- Drama; Monks -- Italy -- Drama; Saints -- Italy -- Drama; Italien; Film; Biographical films; Feature films; Historical films